2017
DOI: 10.1080/09273948.2017.1311925
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Aspect of Intravitreal Ranibizumab Treatment in Neovascular Age-Related Macular Degeneration: A Five-Year Follow-Up

Abstract: Patients with CFH TT genotype responded significantly better to treatment after third year, while patients with CC genotype had a poorer response to IVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Numerous studies have indicated that NLR and PLR are markers of increased systemic inflammation. [11][12][13][14][15][16][17][18][19] One study associated a high NLR with a poor prognosis in trauma patients, particularly those with traumatic brain injury. [25] High NLR and PLR have also been linked to poor outcomes in various diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have indicated that NLR and PLR are markers of increased systemic inflammation. [11][12][13][14][15][16][17][18][19] One study associated a high NLR with a poor prognosis in trauma patients, particularly those with traumatic brain injury. [25] High NLR and PLR have also been linked to poor outcomes in various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] It has been observed that these ratios increase in various eye diseases and are correlated with the severity of the condition. [14][15][16][17][18][19] A study focusing on adult populations with OGI found that high baseline NLR and PLR values were associated with a worse prognosis. [20] Our study aims to evaluate pediatric patients with OGI using the MPOTS and to investigate the impact of NLR and PLR parameters on prognosis and MPOTS scores.…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying mechanism of refractility to treatment is not fully understood and management of these patients is often limited to switching of different anti-VEGFs [49]. Interestingly, several association studies have indicated a role of complement polymorphism in anti-VEGF treatment response (CFH CC genotype), although results are not con rmative and long-term follow up is limited [50,51].…”
Section: Introductionmentioning
confidence: 99%